PAPR Reduction in DCO-OFDM Visible Light Communication Systems Using Optimized Odd and Even Sequences Combination - Wei-Wen Hu (IEEE Photonics Journal)
This paper proposes a novel peak-to-average power ratio (PAPR) reduction scheme, which has several advantages, such as low-complexity candidate construction and no side information (SI) transmission in direct current-biased optical orthogonal frequency division multiplexing (DCO-OFDM) visible light communication (VLC) systems. In the proposed scheme, the candidates can be generated by linearly combining time-domain even and odd sequences with cyclic shift and phase rotation. Even and odd sequences are obtained by adopting an inverse fast Fourier transform on the even and odd parts of a Hermitian symmetry encoded signal, respectively. Furthermore, a deterministic and efficient selection method of cyclic shift and phase rotation is derived to improve PAPR reduction performance and ensure that each candidate is unique, so that the receiver can recover the transmitted candidate signal without the use of SI. Simulation results show that the proposed scheme can achieve comparable PAPR reduction performance with the conventional selected mapping (CSLM) scheme with random and chaotic sequences, but at a considerably low computational complexity. Moreover, the proposed blind SI detection scheme provides almost the same bit error rate (BER) performance as that of the CSLM scheme with a perfect SI detection and symmetric selected mapping for a DCO-OFDM VLC system with 1024 subcarriers and 16-QAM. In contrast to other related time-domain sequences that combine methods used for DCO-OFDM systems, the proposed scheme improves BER performance with a slight increase in computational complexity and PAPR.